Pengembangan Media Busy - Sensory Board untuk Meningkatkan Kemampuan Motorik Halus Anak Slow Learner - Bella Mutiaratanti; Nafila Luthfi Afifah; Revarina Putri Auliya; Mierrina (STKIP Subang, 2026)
Abstract Fine motor development is an important aspect of supporting the independence of early childhood, particularly for children with slow learner characteristics who tend to experience delays in small muscle coordination. This study aims to develop a busy - sensory board as a learning medium to support the improvement of fine motor skills in slow learner children. The research employed a Research and Development (R&D) method with a single subject, a child aged 4 years and 4 months. Data were collected through observation, interviews, and documentation, and analyzed using a descriptive qualitative approach. The results indicate a gradual improvement in the child’s fine motor skills, as evidenced by the transition from full dependence to greater independence in activities such as opening and closing bottles, pulling zippers, and pinching objects. In addition, the child’s sensory responses also showed positive development. Therefore, the busy - sensory board can be considered an effective medium for stimulating fine motor development in slow learner children. Keywords: fine motor skills, slow learner, busy board, sensory board, learning media Abstrak Perkembangan motorik halus merupakan aspek penting dalam menunjang kemandirian anak usia dini, terutama pada anak dengan karakteristik slow learner yang cenderung mengalami keterlambatan dalam koordinasi otot kecil. Penelitian ini bertujuan untuk mengembangkan media busy - sensory board dalam meningkatkan kemampuan motorik halus anak slow learner. Penelitian menggunakan metode Research and Development (R&D) dengan subjek tunggal seorang anak usia 4 tahun 4 bulan. Teknik pengumpulan data meliputi observasi, wawancara, dan dokumentasi, dengan analisis data secara deskriptif kualitatif. Hasil penelitian menunjukkan adanya peningkatan kemampuan motorik halus secara bertahap, ditandai dengan perubahan dari ketergantungan penuh menjadi lebih mandiri dalam aktivitas seperti membuka tutup botol, menarik resleting, dan menjepit benda. Selain itu, respons sensori anak juga mengalami perkembangan positif. Dengan demikian, media busy - sensory board terbukti efektif sebagai alat stimulasi motorik halus bagi anak slow learner. Kata kunci: motorik halus, slow learner, busy board, sensory board, media pembelajaran